Cluster secondary ion mass spectrometry : principles and applications - Mahoney, Christine M., 1975- (Wiley, 2013)
This book describes the importance of the emerging technique Cluster Secondary Ion Mass Spectrometry (SIMS), which is used for the analysis of a range of solid materials, including everything from organic and polymeric materials, to cells and semiconductors. The text covers a wide range of topics, encompassing fundamentals, theory, and applications including cluster sources, organic and polymeric depth profiling, and 3-D imaging in organic and polymeric materials. Written by founders in the field, this guide creates a peerless compendium of knowledge on this cutting edge set of methods.